A rare case of non-Hodgkins lymphoma of testis: case study and review of literature - P. N., Sreeramulu; T. V. K., Karthik Hareen; N., Rakesh; V., Prajith Reddy (International Surgery Journal, 2017)
Primary testicular lymphoma is a rare non-Hodgkin’s lymphoma, usually seen in people around 50 years. It accounts for 1% of all non-Hodgkin’s lymphoma. It usually involves bilateral testes. Orchidectomy followed by chemotherapy is the treatment modality. Central nervous system is the common site for extra nodal site followed by skin, lung, and pleura. A 70 years old male patient presented with complaint of painless swelling of the left testes since 1 year. On examination left testes enlarged in size measuring around 8x5x4 cm. Ultrasound showed features suggestive of malignancy? Seminoma left testes. Orchidectomy was done and sent for histopathological examination. Histopathological report showed features of non-hodgkin’s lymphoma. Patient was started with systemic chemotherapy. 3 cycles of CHOP regimen was given to the patient at 21 days interval. Primary testicular tumour being a rare condition, early diagnosis and treatment with orchidectomy followed by chemotherapy is the first choice. Prognosis is poor. Secondary spread to CNS advocates the use of intrathecal chemotherapy.